Long‐term corrosion behaviour of stainless steels in marine atmosphere. Issue 1 (17th August 2017) - Burkert, A.; Müller, T.; Lehmann, J.; Mietz, J.
Abstract : Nine different stainless steel alloys were exposed for 5 years under marine environment and their corrosion behaviour was compared and assessed. The investigation of four different surface finishes for all alloys tested further enabled to consider industry‐specific features of the surface finish for the material comparison. The results of the exposure tests yield conclusions regarding the influence of alloy composition, surface finish and exposure duration under marine environment. The three duplex stainless steels revealed excellent corrosion resistance even in case of crevices during the 5 years of exposure under the given exposure conditions. Also the molybdenum‐alloyed ferritic steel 1.4521 showed good corrosion resistance comparable to the classical austenitic materials 1.4301 and 1.4404. Abstract : Nine different stainless steel alloys were exposed for 5 years under marine environment. Under the given exposure conditions, the alloy composition and not the surface finish was most decisive for the corrosion behaviour. The three duplex stainless steels investigated revealed excellent corrosion resistance. The molybdenum‐alloyed ferritic steel 1.4521 showed comparable corrosion resistance as the tested austenitic reference materials.